The deciduous genital spines of the moth Peridea anceps (Goeze, 1781): Potential socially transferred materials - Saúl Bernat-Ponce; Jose Vicente Pérez Santa Rita; Carlos Cordero; Joaquín Baixeras (PLoS ONE, 2025)
The genitalia of Lepidoptera are complex structures that evolve rapidly and divergently. The endophallus of many lepidopterans is ornamented with elaborate sclerotized structures known as cornuti. In some species, the cornuti are deciduous and remain within the female genital tract after copulation; the function of these structures is virtually unknown. These structures are a peculiar potential type of secondary “socially transferred material” (the primary materials are spermatozoids, i.e., genetic material), because they probably influence the physiology and behaviour of receivers (i.e., females) but are not molecules that function as allohormones. Such influence could be achieved by acting as mating plugs or via mechanical stimulation of females. The most intriguing and bizarre deciduous cornuti are the so-called caltrop cornuti, star-shaped structures, composed of several rays radiating from a central mass. Despite the presence of caltrop cornuti in at least 400 species, there are no studies of their microscopic structure and mechanism of dislodgement and transference to the female. In this study, we describe in detail the general and microscopic structure of the caltrop cornuti and associated structures of the prominent moth Peridea anceps (Notodontidae). We provide quantitative data of the cornuti and, for the first time, we explain the processes of detachment and transference to the female genital tract; we also describe their distribution inside the female genitalia. We discuss the possibility that one of the functions of deciduous caltrop cornuti is protection against sperm competition, as well as their potential influence on other aspects of the behaviour and physiology of females via mechanical stimulation.